Socioeconomic impact of hosting a national sporting event in Muallim District, Malaysia - Ali Md Nadzalan; Omar Firdaus Mohd Said; Nurul Sazila Rashidin; Nor Fazila Abd Malek; Nur Haziyanti Mohamad Khalid; Rajkumar Krishnan Vasanthi (Sport TK)
In Malaysia, many sporting events had been conducted every year. Unfortunately, less research has been conducted on the benefits and side effects of the events. Thus, the impact of hosting a sport event is not well understood. This study was conducted to determine the impact of a national level sport event hosting, namely Sukan Institusi Malaysia (SUKIPT) (in English: Higher Education Sport) on the socioeconomic aspect among residents in Muallim District, Malaysia. A total of 546 respondents, consisting of athletes, managers, spectators and volunteers were recruited as participants of this study. They were given questionnaires that consisted of elements such as happiness and unity among Muallim residents, tourism and economic chances, interest to sports and healthy lifestyle and views on negative impacts. The results were presented descriptively, and the findings indicated a significant impact of SUKIPT on various aspects, including increased happiness and unity among residents, positive effects on tourism and economic opportunities, enhanced interest in sports and healthy lifestyles, and concerns about negative impacts such as environmental pollution and price increments. This study provides valuable insights into the multifaceted impact of hosting national sports events on the socioeconomic aspects of the host city, and highlights the potential benefits and challenges associated with such events.